2022
DOI: 10.3390/nursrep12020031
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Implementing Evidence-Based Practice among Primary Healthcare Nurses in Saudi Arabia: A Cross-Sectional Study

Abstract: Several studies have been conducted to investigate the barriers to implementing evidence-based practice (EBP) worldwide. In Saudi Arabia, a few studies were conducted in hospital and mental health settings, and no study has explored the topic in primary healthcare settings. This study aimed to examine the barriers perceived by primary healthcare nurses in implementing EBP. This study employed a correlational and cross-sectional design. A total of 284 nurses were surveyed using the BARRIERS scale. Regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
1
18
1
Order By: Relevance
“…However, the level of education did not influence nurses’ attitudes and implementation. These findings were contrary to previous studies that indicated that higher levels of education were related to more positive attitudes and better implementation among nurses in SA, Jordan, Iran, and USA, respectively [ 6 , 11 , 12 , 15 , 24 , 26 , 27 , 28 ]. The finding that the level of education was not associated with nurses’ attitudes and implementation might be due to the barriers all nurses face in the hospitals despite their education level.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the level of education did not influence nurses’ attitudes and implementation. These findings were contrary to previous studies that indicated that higher levels of education were related to more positive attitudes and better implementation among nurses in SA, Jordan, Iran, and USA, respectively [ 6 , 11 , 12 , 15 , 24 , 26 , 27 , 28 ]. The finding that the level of education was not associated with nurses’ attitudes and implementation might be due to the barriers all nurses face in the hospitals despite their education level.…”
Section: Discussioncontrasting
confidence: 99%
“…The barriers to EBM practice can be related to personal, social, and work-related aspects. Overcoming the obstacles to EBM practice is critical for successfully implementing evidence-based practice in primary health care [ 33 , 34 ]. The findings of the present study suggest that age is one of the strongest predictors of evidence-based practice.…”
Section: Discussionmentioning
confidence: 99%
“…The commonest barriers perceived by the present study’s respondents were “patients’ values, concerns, and expectations”, “lack of adequate training in EBM”, “lack of clarity about roles and practice”, and “workplace culture”. Several studies globally carried out have found different barriers [ 33 , 37 ]. A study by Khammarnia et al in Iran stated that lack of human resources and time are their significant barriers [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…An explanation for this result could be provided by a corresponding study in the Austrian nursing context, [53] which showed that a lack of structural prerequisites in particular inhibits the implementation of evidence-based practice, a problem that is also reflected in several international studies. [54][55][56][57] Consequently, a sustainable organizational culture must be created by adapting structural conditions in order to use and further develop this competence acquired during nursing education also in practice. [58] Providing target-oriented information, counselling and instruction is a core competence of Austrian RNs and should contribute essentially to prevention, treatment and rehabilitation [59] as well as to the improvement of specific population's health literacy, [60] but the corresponding competencies (related to Factor 1) were found to be comparatively low.…”
Section: Discussionmentioning
confidence: 99%